Kurdish Emirs in the 16th-Century Ruus Registers - Dehqan, Mustafa (Der Islam, 2019)
Sharaf Khān, author of the Sharaf-nāma, is the most energetic early modern champion of Kurdish history. One problem with the standard account of Sharaf Khān is that it organizes Kurdish history according to the author's own classifications, rather than according to the administrative entities of the overlord empires, the Ottomans and Safavids; and that Sharaf Khān had access only to certain sources which are specific to the principalities. This indicates that one must be careful to use all claims of Sharaf Khān about particular Kurdish emirs, because not all that pertains to the understanding of 16th-century Kurdish emirs is included in the Sharaf-nāma. One way of resolving this inconsistency is to refer to the Ottoman archives. What we want to emphasize in this paper is the importance of the ruus registers for Kurdish history, which, we think, is less widely recognized. In what follows, we shall deal with the Kurdish materials given in the ruus registers.